Peste des petits ruminants virus infection of goats in Bangladesh: Pathological investigation, molecular detection and isolation of the virus (Bangladesh Veterinarian, 2011)
Peste des petits ruminants (PPR), an economically important morbillivirus infection of sheep and goats, is widely distributed in sub-Saharan Africa, Middle East and western and southern Asia including Bangladesh.  A small flock of Black Bengal goats contracted PPR following introduction of new animals. A pathological investigation was conducted on the outbreak, the viral RNA corresponding to F gene was detected by RT-PCR and the virus was isolated in Vero cells. Out of 37 goats 19 (51%) developed clinnical disease, of which 5 (13.5%) died. Goats under one year of age had highest morbidity and mortality with typical signs and lesions of PPR. Viral RNA should be detected in mesenteric and bronchial lymph node tissues. Typical cytopathic effects (CPE) in Vero cells following inoculation of lymph node tissue homogenate were visible at the third passage. However, the replication of virus in cel culture was detected by RT-PCR at the first and second passage in the absence of visible CPE. RT-PCR appears to be a very useful and sensitive tool not only for the detection of PPR virus in clinical samples but also for monitoring the growth or virus in cell culture following inoculation.DOI: http://dx.doi.org/10.3329/bvet.v28i1.8808 Bangl. vet. 2011. Vol. 28, No. 1, 1–7